Adaptive measuring system with dynamic error estimation of the second-order sensor. (December 2021) - Volosnikov, Andrei S.
Abstract: A problem of the dynamic measurement error estimation and correction is considered. The adaptive measuring system with the dynamic measurement error estimation and correction of the second-order sensor is developed. Correction of the dynamic error is achieved by simultaneous restoring and filtering of the sensor input signal being measured. Signal processing consists in determining of the low-pass FIR-filter optimal order by the standard deviation minimization of the dynamic measurement error estimation. Simulation modelling of the proposed measuring system is carried out. A good proximity between input and restored sensor signals as well as between true and estimated dynamic measurement errors is shown. Future works consist in the approach expansion on optimal FIR-filter coefficients adjusting based on dynamic error minimization.